The Role of Higher Education in Reducing the Mismatch between Graduates' Skills and Employer Expectations - Japaridze, Dimitri; Maghlakelidze, Shorena; Shaverdashvili, Ekaterine; Tutberidze, Davit (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
In recent years, increasing emphasis has been placed on the need to match university graduates with the needs of the labor market. This has been challenged by the dissatisfaction often expressed by employers, related to the large discrepancy existing between the knowledge and skills acquired by students in the process of studying at the university and the knowledge and skills needed to be prepared for performance of work. A similar situation exists in Georgia, as shown by the 2019 Skills Mismatch Measurement Report conducted by the European Training Foundation. The report identified a significant gap between the skills acquired and the skills demanded by employers. These mismatches include technical skills as well as personal and interpersonal skills, known as soft skills. Accordingly, the aim of our study was to examine the extent to which higher education reflects the demands of the labor market, i.e. the extent to which the knowledge and skills required by employers correspond to the knowledge and skills actually demonstrated by graduates in the advertised vacancies. To achieve this goal, we used quantitative research. We surveyed employers using a questionnaire to determine their expectations regarding graduates’ skills. Based on the data obtained using the Likert scale, we assessed the necessary skills required by the employer and the skills that graduates demonstrated in interviews or tests. The study confirmed that the challenges and problems in terms of mismatch identified in the above-mentioned fund report remain particularly acute and, accordingly, the level of employer satisfaction is critically low. In this regard, recommendations have been prepared on the role of universities in reducing the mismatch between graduates’ skills and employers’ expectations.